Aliran Dan Pemikiran Kalam Maturidiyah - Arif Arif; Nunu Burhanuddin (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2023)
This paper discusses one of the theological streams within Islam, namely Maturidiyyah, which is divided into Maturidiyyah Samarkand and Maturidiyyah Bukhara. As a reaction to Mu'tazilah, Maturidiyyah, like Asy'ariyyah, is a sect of Ahl al-Sunnah wa al-Jama'ah. This study delineates how the theological thought of al-Maturidi emerged, the background factors, developments after the death of al-Maturidi, the Maturidiyyah thought methodology, and the portrayal of modern Maturidiyyah thought. A qualitative descriptive method is employed with a literature review approach to the Maturidiyyah theological and kalam thought. Rooted in Abu Mansur al-Maturidi, this stream uses rational and verbal evidence to counter Mu'tazilah, Jahmiyyah, and other streams. The evolution of Maturidiyyah is divided into stages of establishment, formation, organization and the foundation of beliefs, as well as expansion and dissemination. Maturidiyyah thought encompasses the obligation to know God, acknowledgment of good and evil, the wisdom and purpose of God's actions, the attributes of Allah, seeing Allah on Judgment Day, and views on major sinners. Modern Maturidiyyah thought emphasizes individual freedom in interpreting and practicing Islamic teachings, active engagement in interfaith dialogue, and maintaining a balance between reason and revelation to uphold the relevance of Islam in the modern era.